Association of serum homocysteine with vitamin B12 and folate levels in women with pre-eclampsia in a tertiary health care center in Nepal - Binod Kumar Yadav; Suvana Maskey; Aseem Bhattarai; Salina Pradhananga; Sabina Shakya; Astha Regmi (BMC, 2024)
Abstract Background Pre-eclampsia is a syndrome that chiefly includes the development of new-onset hypertension and proteinuria after 20 weeks of pregnancy. Pre-eclampsia is one of the major causes of mortality and morbidity in Nepal. Hyperhomocysteinemia may be a cause of the endothelial dysfunction provoked by oxidative stress in pre-eclampsia. This study was designed to evaluate the association of homocysteine with Vitamin B12 and folate in patients with pre-eclampsia. Method An observational cross sectional study was performed in the Gynecology and Obstetrics Department of TUTH involving seventy two subjects with pre-eclampsia. Blood pressure, urinary protein levels, serum homocysteine, Vitamin B12 and folate levels were compared in both mild and severe forms of pre-eclampsia. Concentration of Vitamin B12 and folate were measured using Vitros ECI and homocysteine was measured using CLIA. SPSS 23.0 was used to analyze the data. Tests were performed with Mann Whitney Test and Spearman's rank correlation test. A p-value < 0.05 was considered statistically significant. Results This study showed no significant difference in age and weeks of gestation in both mild and severe forms of pre-eclampsia. Mean concentration of homocysteine was higher (13.1 ± 6.4 micromol/L) in severe Pre-eclampsia as compared to mild cases (7.6 ± 2.8 micromol/L). Mean concentration of folate was lower in severe cases (35.4 ± 24.1 micromol/L) when compared with mild cases of pre-eclampsia (57 ± 23.4 micromol/L). Conclusion Homocysteine levels were increased in severe Pre-eclampsia when compared with mild pre-eclampsia and this finding can be used to predict and prevent complications in patients with pre-eclampsia.